Nonmaternal Care's Association With Mother's Parenting Sensitivity: A Case of Self‐Selection Bias?. Issue 3 (20th May 2013) - Nomaguchi, Kei M.; DeMaris, Alfred
<x xml:space="preserve">Abstract</x> Although attachment theory posits that the use of nonmaternal care undermines quality of mothers' parenting, empirical evidence for this link is inconclusive. Using data from the National Institute of Child Health and Human Development Study of Early Child Care and Youth Development (N = 1, 233), the authors examined the associations between nonmaternal care characteristics and maternal sensitivity during the first 3 years of children's lives, with special attention to selection effects and moderation by resource levels. Findings from fixed‐effects regression models suggested that, on average, there is little relationship between nonmaternal care characteristics and maternal sensitivity, once selection factors are held constant. Some evidence of moderation effects was found, however. Excellent‐quality care is related to more sensitivity for mothers with lower family income. Poor‐quality care is related to lower sensitivity for single mothers, but not partnered mothers. In sum, nonmaternal care characteristics do not seem to have as much influence on mothers' parenting as attachment theory claims.